2022
DOI: 10.1186/s13104-022-06197-8
|View full text |Cite
|
Sign up to set email alerts
|

An integrative telehealth platform managed by nurses

Abstract: Objective Our aim was to assess the feasibility and preliminary results of implementing a telehealth system, Alice Agora, as a tool for optimizing health delivery in a new primary care-based health system. Results We had 4193 consultations over the last 6 months (February and August 2021). Preliminary results show patients high level of satisfaction (Consumer satisfaction score of 4.92). The chief complaints were related to upper respiratory tract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Involvement of nurses in telehealth or e‐health was described in 43 studies (Ahmed et al., 2013; Ajay et al., 2016; Anger et al., 2020; Anson et al., 2022; Bosworth et al., 2011; Bove, 2010; Carlisle & Warren, 2013; Chang et al., 2007; Clarke et al., 2018; Cook et al., 2007; Datta et al., 2010; de Moraes et al., 2022; Delahunty‐Pike et al., 2023; Engel et al., 2015; Fox & McCorkle, 2018; Grisot et al., 2019; Hoffman et al., 2023; Howland et al., 2020; Hui et al., 2022; Hunkeler et al., 2000; Iversen et al., 2020; Jackson et al., 2017; Jeong et al., 2018; Jordan et al., 2011; Kwak et al., 2021; Mallow et al., 2018; Mammen et al., 2020; Momin et al., 2022; Moriyama et al., 2021; O'Brien, 2022; Parham et al., 2010; Parham et al., 2023; Pichayapinyo et al., 2019; Ramakrishnan et al., 2020; Rosenman et al., 2006; Schofield et al., 2005; Shaw et al., 2013; Stone et al., 2010; Teo et al., 2024; Turner et al., 2009; Wakefield et al., 2011; Walker et al., 2015; Williams et al., 2001), with nurses using devices (both telephone and videoconferencing) to counsel patients and gather medical information. This included interpreting electronic or patient reported data such as patient biometrics (Chang et al., 2007; Clarke et al., 2018; Grisot et al., 2019; Howland et al., 2020; Pichayapinyo et al., 2019; Schofield et al., 2005; Stone et al., 2010; Turner et al., 2009; Wakefield et al., …”
Section: Resultsmentioning
confidence: 99%
“…Involvement of nurses in telehealth or e‐health was described in 43 studies (Ahmed et al., 2013; Ajay et al., 2016; Anger et al., 2020; Anson et al., 2022; Bosworth et al., 2011; Bove, 2010; Carlisle & Warren, 2013; Chang et al., 2007; Clarke et al., 2018; Cook et al., 2007; Datta et al., 2010; de Moraes et al., 2022; Delahunty‐Pike et al., 2023; Engel et al., 2015; Fox & McCorkle, 2018; Grisot et al., 2019; Hoffman et al., 2023; Howland et al., 2020; Hui et al., 2022; Hunkeler et al., 2000; Iversen et al., 2020; Jackson et al., 2017; Jeong et al., 2018; Jordan et al., 2011; Kwak et al., 2021; Mallow et al., 2018; Mammen et al., 2020; Momin et al., 2022; Moriyama et al., 2021; O'Brien, 2022; Parham et al., 2010; Parham et al., 2023; Pichayapinyo et al., 2019; Ramakrishnan et al., 2020; Rosenman et al., 2006; Schofield et al., 2005; Shaw et al., 2013; Stone et al., 2010; Teo et al., 2024; Turner et al., 2009; Wakefield et al., 2011; Walker et al., 2015; Williams et al., 2001), with nurses using devices (both telephone and videoconferencing) to counsel patients and gather medical information. This included interpreting electronic or patient reported data such as patient biometrics (Chang et al., 2007; Clarke et al., 2018; Grisot et al., 2019; Howland et al., 2020; Pichayapinyo et al., 2019; Schofield et al., 2005; Stone et al., 2010; Turner et al., 2009; Wakefield et al., …”
Section: Resultsmentioning
confidence: 99%
“…Finally, we found few works in the literature about customer satisfaction using telemedicine, for example, regarding services using telemonitoring and teleconsulting [27], a satisfaction questionnaire to measure health care professionals' satisfaction [28], a specific questionnaire to assess the quality of the service and the patient satisfaction [29] or using telehealth platforms managed by nurses [30]. To our knowledge, there are no data about televisit and telecounselling in post-myocardial infarction patients; this study examined the users' satisfaction, reporting the majority of patients being satisfied not only with televisit itself, but also with the technicians' counselling and contact at a distance to improve self-management of their diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These technologies facilitate the collection and incorporation of patient-reported information into clinical practice. Electronic Patient Reported Outcomes (e-PRO) evaluation systems allow for continuous standardized patient assessments and have resulted in a lower response burden and better user experience compared to paper-based PRO evaluations (1)(2)(3). Additionally, e-PRO systems contain features that enable progress tracking by both clinicians and patients providing real-time assessment and feedback (2).…”
Section: Introductionmentioning
confidence: 99%
“…These patients are supported by a nursing team that are guided by evidence-based medicine protocols. Our recent research has shown that 64% of acute conditions were resolved with the assistance of our telehealth platform, mainly driven by nurses ( 1 ). Thus, acute conditions are already partly being addressed by our digital ecosystem.…”
Section: Introductionmentioning
confidence: 99%